Metabolic Syndrome Impairs Executive Function in Bipolar Disorder - Dalkner, Nina; Bengesser, Susanne A.; Birner, Armin; Fellendorf, Frederike T.; Fleischmann, Eva; Großschädl, Katja; Lenger, Melanie; Maget, Alexander; Platzer, Martina; Queissner, Robert; Schönthaler, Elena; Tmava-Berisha, Adelina; et al. (Frontiers in Neuroscience, 2021)
Background: Metabolic syndrome (MetS) is more prevalent in individuals with bipolar disorder and has a negative impact on cognition, in particular on executive function, which is already impaired in individuals with bipolar disorder compared to healthy controls. Methods: In a cross-sectional study, we compared 148 euthymic patients with bipolar disorder and 117 healthy controls in cognitive function depending on the diagnosis of MetS. A neuropsychological test battery was used including the Trail Making Test A/B, Stroop Color and Word Interference Test, the d2 Test of Attention Revised, and the California Verbal Learning Test. In addition, MetS variables as well as the defining variables waist circumference, serum triglyceride levels, high-density lipoprotein cholesterol levels, blood pressure, fasting glucose levels, and body mass index were compared between patients and controls. In addition, illness-related variables were associated with MetS in individuals with bipolar disorder. Results: The prevalence of MetS in patients with bipolar disorder was higher than in controls (30.4 vs. 15.4%). Patients with bipolar disorder with MetS had impaired executive function compared to patients without MetS or healthy controls with and without MetS (p = 0.020). No MetS effects or interaction MetS × Group was found in attention/processing speed (p = 0.883) and verbal learning/memory (p = 0.373). Clinical variables (illness duration, suicidality, number of affective episodes, medication, age of onset, and history of psychosis) did not relate to MetS in bipolar disorder (p > 0.05). Conclusion: Bipolar disorder comorbid with MetS bears additional risk for impaired executive function. Executive function includes action planning, inhibition, and impulse control and could play a critical role in keeping long-term goals in mind associated with gaining and maintaining a healthy weight.